Importance of quality indicators in the healthcare – in case of musculoskeletal rehabilitation – - Dénes, Rita (International Journal of Engineering and Management Sciences, 2016)
Nowadays the term of management is so popular. It has an essential role in the professional life, moreover in the every day life too. Creating and using the quality indicators (one of the qualiy management tools) contribute to the improvement of the operation of the healthcare system and to the development of the quality of healthcare services. The aim of the paper is to define service quality and its dimensions in healthcare and to highlight the role of quality indicators. The research calls attention to the absence of indicators measuring the different aspects of quality directly, the difficulties of measuring service quality and the need of establishment of more specific measures in healthcare. A special area of healthcare, there habilitation of musculo skeletal diseases will be discussed. As a research my approach is to define all the indicators that are already used in this area of the healthcare. This examination is extremely important because one of the most commonailments are the musculo skeletal diseases and their number is just increasing.The paper is mostly descriptiv and follows analitical methods based on the international and Hungarian professional studies, informations. To access databases I was helped by the OSAP (National Statistical Data CollectionProgramme). Besides the importance of quality indicators the research calls for the need for more specific measures. On the other hand, the value of the paper lies in collecting the problems, defaults and improving areas of a specific healthcare field.